(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Despite some progress, in Bangladesh access to high quality essential maternal healthcare remains inadequate. Women living in urban slums may face additional obstacles to maternal healthcare, but evidence remains limited. The study aims to explore the patterns of maternal healthcare utilisation in urban slums. Methods: This cross-sectional survey was conducted in April 2022 using an established health and demographic surveillance system operating in Dhaka North, Dhaka South and Gazipur city corporations. Six hundred thirty five married women of reproductive age with a baby aged ≤12 months were interviewed. Univariate and multivariate analysis were done to determined the factors affecting utilisation of maternal healthcare services. Results: Overall, 36% of respondents had at least four antenatal care checkups, 56% had facility-based delivery, 58% had delivery with a skilled attendant and received postnatal care within two days of delivery. Use of essential services was low among uneducated women. Geographical differentials were found, raising questions about the low antenatal care and high private facility delivery in Gazipur. Many women opt for private delivery care, and 35% reported having a C-section. Conclusion: Attention is needed across the whole pregnancy journey to improve access to high quality affordable antenatal care, delivery care and postnatal care for urban slum women. A complex of factors appears to be at play, with women’s awareness, household decision-making, and provision of accessible, affordable, high-quality services all requiring action by policy makers.